Venture Capitalists Investment Incentives Under Public Equity Schemes - Andrea Schertler (Kiel Institute for World Economics (IfW), 2002)
This paper analyses the impact of public equity schemes on venture capitalist's incentives to finance start-up enterprises and to support the management teams. In a double-sided moral hazard model, it is shown that experienced venture capitalists, who have already financed start-up enterprises, reduce their intensity of management support under public equity schemes. However, public equity offers inexperienced venture capitalists, who have not yet financed start-up enterprises because of insuf-ficient experience, incentives to enter the venture capital market so that they can start to accumulate experience.
Keywords: L14; G28; G24; D82; 330; Double-sided moral hazard; public equity; venture capital; Risikokapital; Öffentliche Kapitalbeteiligung; Subvention; Unternehmensgründung; Finanzierungstheorie; Moral Hazard; Theorie